The Observational Study Financial Fraud Offense Themes and Financial Fraud Risk of Money Laundering to Increase Financial Global Sustainability Compliance - Patel, Sina; Kasztelnik, Karina; Zelihic, Maja (Journal of Accounting and Finance, 2023)
American society could benefit from the results of the study. The banking and financial industries ought to be prepared for the future and continue to adapt to new emerging threats, varying consumer classification, and changing environment. Banking and financial services institutions play a substantial role in the community. By changing and developing new policies and procedures, these organizations can work towards effective money laundering and financing fraud prevention compliance plans. Additionally, banks and financial services institutions may clarify and strengthen customer due diligence requirements to protect their organizations and reduce financial fraud risks. The implications for positive social change may include the possibilities to develop new compliance strategies and strengthen existing regulatory mechanisms to help compliance managers, reduce the risk of bank failures, increase employment opportunities, and promote public awareness by educating consumer about financial fraud risks.